2021
DOI: 10.1186/s13619-020-00066-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HOXA9 upregulates NF-κB signaling to promote human hematopoiesis and alter the hematopoietic differentiation potentials

Abstract: Background The HOX genes are master regulators of embryogenesis that are also involved in hematopoiesis. HOXA9 belongs to a cluster of HOX genes that play extensively studied roles in hematopoiesis and leukemogenesis. Methods We established HOXA9-inducible human embryonic stem cells (HOXA9/hESCs) with normal pluripotency and potential for hematopoiesis, which could be used to analyze gene function with high accuracy. HOXA9/hESCs co-cultured with ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…When NF-κB signaling was inhibited by its inhibitor (QNZ) or by siRNA against NFKB1 , except for further increased apoptosis, all other effects of P18 overexpression at the late stage were counteracted (Fig. 6 b,c), which was very similar to the phenomenon caused by HOXC4 and HOXA9 overexpression at the late stage 23 , 24 , and indicated that these genes probably share common mechanisms to promote hematopoiesis with the aid of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…When NF-κB signaling was inhibited by its inhibitor (QNZ) or by siRNA against NFKB1 , except for further increased apoptosis, all other effects of P18 overexpression at the late stage were counteracted (Fig. 6 b,c), which was very similar to the phenomenon caused by HOXC4 and HOXA9 overexpression at the late stage 23 , 24 , and indicated that these genes probably share common mechanisms to promote hematopoiesis with the aid of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 70%
“…At the early stage P18 overexpression can block the early hematopoietic differentiation, which is similar to the effects of RUNX1b/c that can be partially rescued by inhibition of TGF-β signaling 1 . At the late stage it can broadly promote the hematopoietic differentiation, which is similar to the effects of HOXA9 and HOXC4 23 , 24 that can be counteracted by inhibition of NF-κB signal pathway, and enhance the expression level of key genes of this pathway. Therefore, we speculated that P18 function ought to be closely related to TGF-β and NF-κB signaling at the early and late stage of hematopoiesis respectively according to our previous researches and performed further exploration based it.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations